Students Participating as Ambassadors for Research in Kentucky (SPARK): A health equity undergraduate research training program - Ariel A. Arthur; Rebecca L. deLacerda Allen; Fidelis Y. Sesenu; Maxwell A. Groznik; Carrie B. Oser; Justin X. Moore; Jessica R. Thompson; Alexis N. James; Madeline N. Dunfee; Philip A. Kern; Nancy E. Schoenberg (Journal of Clinical and Translational Science)
The Students Participating as Ambassadors for Research in Kentucky (SPARK) program provides novel health equity research training and targeted mentorship for undergraduates, particularly those from groups underrepresented in the biomedical and behavioral research and workforce. SPARK aims to address inadequate diversity in the medical and scientific research fields by providing comprehensive research mentorship and skill-building. Unlike most existing research training programs that are brief, focus on laboratory research, or are limited to graduate students and junior faculty, SPARK delivers a 16-month intensive behavioral and population health science training, equipping students with needed tools to conceptualize, plan, execute, and analyze their own health equity research study. Trainees complete didactic coursework on health equity, study design and proposal development, data analysis, and ethics. Students receive a stipend and research expenses, and multiple mentors guide them in creating original research projects for which they serve as Principal Investigator. Students disseminate their findings annually at an academic research conference as a capstone. Evaluation data from the first three cohorts suggest SPARK has been pivotal in preparing students for graduate studies and research careers in health equity and behavioral and population health sciences, providing strong support for further investments in similar undergraduate research training models.